Faktor Yang Menyumbang Kepada Ketidakmampuan Pemilikan Rumah Dan Kesannya Dalam Kalangan Isi Rumah Bandar M40 Di Pulau Pinang - Azahar, Nur Shafiqah (2024)
Homeownership is a crucial element in ensuring human well-being. However, there are notable distinctions concerning the matter of home ownership between the B40 and M40 household segments. The majority of incentives for home ownership are directed towards the B40 households, while the M40 households receive less emphasis. This scenario particularly impacts the M40 income group in owning their own homes. Therefore, this study aims to examine the factors influencing the ability to own a house among M40 urban households in Penang. Additionally, the study analyzes the implications of the inability to own a house and provides recommendations to enhance homeownership among M40 urban households in Penang. The study adopts a qualitative approach through semi-structured interview method. The purposive sampling techniques are employed to select 20 study participants and 3 informant who meet the predetermined criteria. The findings revealed several factors that affect the ability to own a house among M40 urban households in Penang, including housing costs, house criteria, household income, savings, and housing loans. Findings of this study also revealed four main effects of the inability to own a home among urban M40 households in Penang, including financial, social, emotional, and well-being and safety effects. Additionally, the study identified several recommendations to address the issue of homeownership affordability among urban M40 households in Penang, such as expanding targeted housing schemes, government housing initiatives and collaborations, balancing affordability and prices, and providing financial management suggestions for M40 urban households. The main implication of this study is the importance of examining the issue of homeownership affordability comprehensively encompassing various perpspectives or dimensions by identifying the factors and resulting effects among urban M40 households, with the aim of formulating more effective policies and strategies to enhance societal well-being.